Effect of Cobble Content on the Shear Behaviour of Sand-Cobble Mixtures - Chuang Wang; Jinyu Dong; Zhiquan Huang; Jianjun Zhou; Jihong Yang (Advances in Civil Engineering)
The sand and cobble stratum is a kind of mechanically unstable stratum. Shield machine often encounter problems such as difficulty in excavation, cutterhead wear, and poor slag discharge of the spiral dumper while constructing in this kind of stratum. Considering the complexly and variety of the material composition and structure of this stratum, the sand and cobble stratum in China, Chengdu Subway Line 7, Chadianzi-Yipintianxia Station, was selected to conduct indoor large-scale direct shear tests to systematically study the effects of cobble content (CC) on the shear strength and shear properties of sand and cobble soil. The test results showed that the shear strength and angle of internal friction of sand and cobble soil nonlinearly increased with CC, and the shear strength and angle of internal friction slightly increased when CC was less than 40%. The shear strength and angle of internal friction of sand and cobble soil significantly increased after CC reaching 40%. The shear stress-shear displacement curve has three stages, including the elastic deformation stage, yield stage, and hardening stage. The CC had a control effect on the strength and deformation characteristics of sand and cobble soil. The shear stress-displacement curve of sand and cobble soils with CCs of 20% and 80% can be fitted as an exponential model, while the shear stress shear displacement curves of sand and cobble soils with CCs of 40% and 60% are hyperbolic. For sand and cobble soil with same CC, the larger the vertical stress is, the larger the normal displacement is.